The Association Between Dietary Pattern, Physical Activity, Sedentary Activity And Overweight at SMA Negeri 5 Surabaya - Wismoyo Nugraha Putra (Universitas Airlangga, 2017)
ABSTRACT Overweight is health problem that occurs because of imbalance between input and output energy causing the accumulation of excessive fat tissue in the body. There are several factors that can lead to overweight are excess of dietary pattern, physical activity and sedentary lifestyle. The purpose of this research is to analyze the relationship between dietary pattern, physical activity and the sedentary lifestyle with overweight incidence at SMA Negeri 5 Surabaya. This research is analyitic observational with cross sectional design. Accessible population sizes in this research are 679 students with numbers of samples are 157 students (simple random sampling). Data processing by using computer application with the univariate and bivariate analysis. The results analysed using chi square test with α = 0.05. The results showed correlation between sex (p = 0.041), mother's job (p = 0.025), dietary pattern (p = 0.035) and physical activity (p= 0.015) with overweight. There was no correlation between parent's education, father's job, parent's income, student's pocket money, sedentary lifestyle with overweight. Suggestions for school to held morning gymnastics twice a week, also extends the extracurricular duration. Teenagers are expected to increase and balance the diet consumption. Keywords: physical activity, sedentary lifestyle, overweight, dietary pattern